Adult heart transplant: indications and outcomes - Alraies, M. Chadi (Pioneer Bioscience Publishing Company, 2014)
Cardiac transplantation is the treatment of choice for many patients with end-stage heart failure (HF) who remain symptomatic despite optimal medical therapy. For carefully selected patients, heart transplantation offers markedly improved survival and quality of life. Risk stratification of the large group of patients with end-stage HF is essential for identifying patients who are most likely to benefit, particularly as the number of suitable donors is insufficient to meet demand. The indications for heart transplant and review components of the pre-transplant evaluation, including the role for exercise testing and risk scores such as the Heart Failure Survival Score (HFSS) and Seattle Heart Failure Model (SHFM) are summarized. Common contraindications are also discussed. Outcomes, including survival and common complications such as coronary allograft vasculopathy are reviewed.